The satisfaction level of SMES with smart factory introduction using cluster analysis - Yoon Oh, Jeong; Hyun Choi, Sang; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is necessary to confirm whether the introduction of smart factory is moving in the right direction for SMEs applying the basic stage of Smart Factory. We would like to investigate the characteristics of the company according to satisfaction levels of Smart Factory introduction.Methods/Statistical analysis: We collected the questionnaire of companies applying the basic level of Smart Factory and conducted a cluster analysis on the whole data. Four groups were classified into two groups with low satisfaction level and two groups with high satisfaction level. To investigate the characteristics of each group, we conducted a cluster analysis of each group to identify the difference according to satisfaction.Findings: The group with low satisfaction was divided into two clusters. One applied MES and the improvement of defect rate is as low as 8%, the other applied ERP and the expectation of quality improvement is high. The groups were divided into three groups. The first one is the group that wants to proceed to next stage regardless of the governmental support without staying at the basic stage. The second one is the group that applied MES and considers governmental support important when progressing with the intermediate 1st stage. And last one is the group that has the highest rate of Equipment linkage, productivity improvement, sales growth and improvement of defect rate.Improvements/Applications: This paper will help to benchmark companies that are introducing smart factories. However, it would be a better study if we carry out research that increases the number of data and predicts satisfaction.Â Â